Motives for Mergers and Acquisitions in the Nepalese Perspective - Pathak, Hari Prasad (Economic Literature, 2018)
This paper attempts to identify the motives of mergers and acquisitions in the Nepalese financial sector.Questionnaire survey method is used to obtain the views of randomly selected 122 bankers of 21 post-merged financial institutions.A two-stage multivariate procedure is used to identify the important factors that drive the merger of financial institutions.In the first stage, an exploratory factor analysis is performed using ten statements that were put in the Likert scale in the questionnaire. In the second stage, important motives of mergers are determined by conducting an ordinary least squares regression using the factors extracted from factor analysis. It checks the internal consistency and reliability of the data using the Cronbach’s Alpha. The paper concludes hat the three most important motives for mergers of Nepalese financial institutions are: (i)meeting the regulatory requirement of paid up capital, (ii) realization of economies of scale and scope, and (iii) generation of efficiencies due to synergistic gains. Economic Literature, Vol. XIII August 2016, page: 9-18